Profitabiltas Usahatani Padi Sawah Tadah Hujan Kabupaten Maros - Arifin, Arifin (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
Efforts to increase income and maintain the existence of rice farming must be a priority for agricultural development. High productivity will lead to high farmer acceptance with efficient production costs so that farmers' income and farm profitability will increase. The purpose of this study was to analyze the profitability of rainfed lowland rice farming. This research was conducted in Soreang Village, Lau District and Bonto Mate'ne Village, Marusu District, Maros Regency. The total population of the study was 334 people and the sample was 15% of the total population, namely 50 farmers. Farmer samples were taken using simple random sampling method. Data collection techniques used are observation, interviews, and documentation. The types of data are qualitative and quantitative data. There are two sources of data, namely primary and secondary data. The data analysis method used is profitability analysis, namely Gross Margin, Net Farm Income, Net Profi Margin, and Return on Investment. The results of this study indicate that rainfed lowland rice farming in Maros Regency uses profitability analysis, namely the efficient Gross Margin produces net profits, Net Farm Income gets a profit or net income, Net Profit Margin gains increase (NPM > 5%), and Return on Investment in farming Rainfed lowland rice is profitable to implement (ROI > 50%). In order to increase the profitability of rice farming, it is necessary to use urea and phonska fertilizers according to the recommendations so that production can be increased.